DISEÑO Y EVALUACIÓN A CORTO PLAZO DE UN APARATO MIOFUNCIONAL Y FORMULACIÓN DE UN PROTOCOLO PARA TRATAMIENTO TEMPRANO DE PACIENTES CON MICROSOMIA HEMIFACIAL (2009)
Objective: To describe the use of a myofunctional device as a stimulator of the affected side condylar growth in patients with hemifacial microsomia (HFM).Methods: A myofunctional device was used in four patients with HFM, ages 10.8 ± 2.1 years who attended the Cleft Lip and Palate Clinic at the Santo Tomas University. This myofunctional appliance consisted of a simple flat tracks designed acrylic indirect asymmetrically in the vertical and sagittal planes.Results: It was observed a correction of facial asymmetry in two patients and two remained unchanged. This correction was achieved by an increase in condylar height in one case and the other by a dentoalveolar compensation.Conclusions: Early treatment in patients with HFM is effective and accurate if it has the support of patients and their guardians. In this study, it was seen a decrease in the difference in condylar height that although no statistically significant importance, is a relevant biological aspect. It also managed to reduce the inclination of the occlusal plane in one patient.